(3efgL GdSjhWi ai OQGSI GdeJTGHg GddaXi (B/ s - (3QaGYi eWdb GdUdjdis; (3eMeO YHOGdeLjO GdWhjd (B: s; (3eMeO YjO MSf YHOGdfHi (B: s ((3GdbGgQI (B: s (3QaGYi eWdb GdUdjdi (B: s, 2021)
(3JNU gPg GdOQGSI GdeJTGHg GddaXi ai GdbQBf GdcQje(B: (3OQGSI JMdjdjI dcd BjJjf bQBfjJjf JTGHgJG(B: (3h GNJdaJG HGdJbOje h GdJCNjQ(B: (3Ch HGdPcQ h GdMPa(B: (3Ch HGNJdGa UjZ HYV cdeGJgeG(B: (3Ch HGSJHOGd cdeI Ch JQcjH ai EMOGgeG HcdeI Ch JQcjH ai GdCNQi(B. (3JTJed GdOQGSI Ydi ebOeI h JegjO h CQHYI aUhd h NGJeI jdjgG agGQS GdHMK(B. (3JSdW GdebOeI GdVhA Ydi CgejI GdOQGSI h CgOGagG h GdOQGSGJ GdSGHbI h eLGd GdHMK h efgLg h NWJg(B. (3h CeG GdJegjO ajJfGhd SeGJ efgL GdSjhWi ai OQGSI GdeJTGHg GddaXi ai cJHg(B. (3h CeG GdaUd GdChd ajOQS JhLjg GdSjhWi dbVGjG GdGSJHOGd ai CQHYI eHGMK(B: (3GdGSJHOGd GdGSei(B: (3h GdGSJHOGd GdMQai(B: (3h GdGSJHOGd GdaYdi(B: (3h GdGSJHOGd ai ahGUd GdBjGJ(B. (3h CeG GdaUd GdKGfi ajOQS JhLjg GdSjhWi dbVGjG GNJdGa GdUjZI ai SJI eHGMK(B: (3NeSI JJYdb HGNJdGa UjZI GdGSe(B: (3h eHMK dGNJdGa UjZI GdaYd(B. (3h CeG GdaUd GdKGdK ajOQS JhLjg GdSjhWi dbVGjG GdJbOje h GdJCNjQ ai eHMKjf(B: (3GdJbOje h GdJCNjQ Hjf GdeJYGWajf(B: (3h JbOje eJYdb GdaYd h JCNjQg(B: (3h CeG GdaUd GdQGHY ajOQS JhLjg GdSjhWi dbVGjG GdPcQ hGdMPa ai KdGKI eHGMK(B: (3GdYWa h JQcg(B: (3h MPa GdMQa ai ZjQ GdYWa(B: (3h MPha CNQi(B. (3h CeG GdNGJeI aJTJed Ydi Cge GdfJGFL GdJi JhUd GdHMK EdjgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh h GdUQa h GdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdSjhWis; (3GdbQBf GdcQjes; (3GdeJTGHg GddaXis